satisfaction analysis of quality of service in Hotel Furaya Pekanbaru - Syafriandi, Raja; Syafriadi, Raja; ', Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study was conducted in the area of the object of research is Pekanbaru Pekanbaru Furaya hotel is located at Jalan Sudirman, Pekanbaru-Riau. The purpose of this study was to determine the level of satisfaction with the quality of service at the hotel to find out Furaya Pekanbaru and satisfaction improvement strategy services on Furaya Hotel Pekanbaru. The sampl es in this study were 100 people, the determination of the number of samples based on the method Slovin. While the data analysis technique used is the Importance Performance Analysis (IPA).Based on the results of analysis show that in general the quality of existing services on Furaya Hotel Pekanbaru has good / satisfactory for the hotel customers. Dimensions sequentially most good / satisfactory is Tangible (90.9%), Responsiveness (84.3%), Assurance (79.4%), Emphaty (78.1%) and Reliability (76.3%).The aspects that need to be improved is the ability of employees to communicate, the alertness of employees, employee courtesy, meeting the needs of employees. While aspects that need to be maintained is adequate physical facilities, employee service, employee skills, feeling safe, relationship and a suggestion box.Keywords: Customer Satisfaction, Tangible (Tangible), Reliability (Reliability), Responsiveness (Readiness), Assurance (Assurance) and Emphaty (Attention).